Long-term (1979-2019) changes in the Black Sea storminess - Tahtaci, Kadir; Ayat, Berna (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2022)
Purpose: This study aims to reveal the long-term (1979-2019) trends in the characteristics of sea storms along the Black Sea shoreline. Long-term trends of storm durations, wave heights, and an annual number of storms were studied for this purpose. The objectives of the study also include revealing the seasonal characteristics of the long-term trends and the relations to the climate oscillation indices. Theory and Methods: Singular storms were determined by considering the threshold value at which wave height exceeds twice the average wave height. Thus, annual storm numbers, average, total, and maximum storm durations, average, average peak, and maximum wave heights of storms were obtained for each year from time series consisting of hourly data obtained from the spectral wave model. Theil-Sen method was used to determine long-term upward or downward trends in these parameters, and the Mann-Kendall test was used to determine the significance levels of the determining trends. Analyses were carried out on a monthly basis to determine the seasonality of storminess in change. The relations of the climate long-term oscillation indices with the storminess of the Black Sea were determined. Results: The results of the study indicated a downward trend of 2 storms/decade along the coast of Odessa and the west of the Crimean Peninsula, and a 1 cm/decade increase in the average wave heights of storms. Seasonal analysis revealed a statistically significant upward trend in all storm parameters in the August-October term in the western Black Sea. The number of storms and wave heights showed positive correlations at a confidence level of 95% with PNA and AMO indices along the northern coasts of the Black Sea. Conclusion: Sea storms present statistically significant long-term trends along the Black Sea shoreline.
Keywords: Sea storm; Trend analysis; The Black Sea; Climate oscillation index; COASTAL REGIONS; WAVE CLIMATE; LEVEL RISE; THRESHOLDS; TRENDS; WIND; VARIABILITY; STORMS; MODEL; PART; Engineering